2018
DOI: 10.3892/mmr.2018.8575
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile analysis of the progression of carotid atherosclerotic plaques

Abstract: The present study aimed to examine the universal gene expression signature and the underlying molecular mechanisms involved in the progression of carotid atherosclerotic plaques. The gene expression dataset, GSE28829, containing 13 early and 16 advanced carotid atherosclerotic plaques was selected for analysis. The differentially expressed genes (DEGs) were identified and analyzed using bioinformatics analyses, including cluster analysis, Gene Ontology (GO) and pathway enrichment analyses. Finally, a protein-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
1
14
0
1
Order By: Relevance
“…GO biological process enrichment analysis showed that up-regulated DEGs are mainly related to immune-inflammatory responses, cell proliferation, differentiation and chemotaxis, response to lipids, reactive oxygen species metabolic process and cell death, which confirmed that cell proliferation and differentiation, cell adhesion, immune inflammation, and lipid metabolism are well associated with atherosclerosis [25]. Meanwhile, our analysis showed that the down-regulated DEGs are involved in muscle contraction, which is in agreement with the results in human carotid atherosclerotic plaque from Liu et al [26]. These results supported that lipid metabolism, oxidative stress and immune-inflammatory responses drive the development of atherosclerosis, which is consistent with the enrichment analysis results of hallmark gene sets in GSEA.…”
Section: Discussionsupporting
confidence: 92%
“…GO biological process enrichment analysis showed that up-regulated DEGs are mainly related to immune-inflammatory responses, cell proliferation, differentiation and chemotaxis, response to lipids, reactive oxygen species metabolic process and cell death, which confirmed that cell proliferation and differentiation, cell adhesion, immune inflammation, and lipid metabolism are well associated with atherosclerosis [25]. Meanwhile, our analysis showed that the down-regulated DEGs are involved in muscle contraction, which is in agreement with the results in human carotid atherosclerotic plaque from Liu et al [26]. These results supported that lipid metabolism, oxidative stress and immune-inflammatory responses drive the development of atherosclerosis, which is consistent with the enrichment analysis results of hallmark gene sets in GSEA.…”
Section: Discussionsupporting
confidence: 92%
“…Further VINC was also found to stimulate tumor progression by increasing PI3K activation of phosphatidylinositol ( 3 , 4 , 5 )-triphosphate in cancer cells ( 34 ). VCL gene expression was found to be significantly elevated in GC tissues, indicating that VCL may contribute to GC progression by stimulation of tumor malignancy and its invasiveness ( 35 ). Targeting the depletion of VCL by anticancer agents may help to overcome cell metastasis and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases DEGs are related to immune response and maintain chronic inflammatory process, wich indicates a significant role of the immune response in the pathogenesis of atherosclerosis [9]. The analysis of DEGs profile in atherosclerotic carotid plaque revealed that upregulated genes were associated with inflammatory response and chemotaxis signal pathways within the immune system [10]. Downregulated genes were associated with contraction and cellular cytoskeleton structure of the vascular smooth muscle cells [10].…”
Section: Risk Factors For Atherosclerosismentioning
confidence: 99%
“…The analysis of DEGs profile in atherosclerotic carotid plaque revealed that upregulated genes were associated with inflammatory response and chemotaxis signal pathways within the immune system [10]. Downregulated genes were associated with contraction and cellular cytoskeleton structure of the vascular smooth muscle cells [10]. Furthermore, the analysis of DEGs showed that genes associated with antigen presentation are of key importance in development of atherosclerotic lesions [9].…”
Section: Risk Factors For Atherosclerosismentioning
confidence: 99%